The intervention of Mobile Internet on Sports Behavior and Sports Awareness of College Students - Zhimei Xue; Weiting Jiao; Guolin Li, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Mobile internet information has an unintended effect on college students’ sports behavior and awareness, although the specific implications have not been widely discussed. Existing research focuses primarily on behavioral science and sports communication. Using prior research as a foundation, this article examines the intervention of mobile internet on the sports behavior and awareness of college students. Specifically, an intervention event network was built and subjected to static structural analysis to determine the influence of mobile internet on college students’ sports behavior and awareness. Then, using system event analysis, a well-established technique in complex system research, the interactive relationship between different intervention events in the network was thoroughly analyzed, and the composite degree of influence between them was assessed. The integrated fuzzy-interpretative structural model was then used to deduce the event-based hierarchy model’s core logic and action mechanism. Finally, the proposed paradigm was demonstrated to be effective via experiments.